Bidirectional Interaction between Phyllospheric Microbiotas and Plant Volatile Emissions. (October 2016) - Farré-Armengol, Gerard; Filella, Iolanda; Llusia, Joan; Peñuelas, Josep
Abstract : Due to their antimicrobial effects and their potential role as carbon sources, plant volatile organic compound (VOC) emissions play significant roles in determining the characteristics of the microbial communities that can establish on plant surfaces. Furthermore, epiphytic microorganisms, including bacteria and fungi, can affect plant VOC emissions in different ways: by producing and emitting their own VOCs, which are added to and mixed with the plant VOC blend; by affecting plant physiology and modifying the production and emission of VOCs; and by metabolizing the VOCs emitted by the plant. The study of the interactions between plant VOC emissions and phyllospheric microbiotas is thus of great interest and deserves more attention. Trends: There is a large body of literature describing how plants emit a large array of volatile organic compounds (VOCs) from leaves, stems, fruits, and flowers that allow them to interact with their biotic and abiotic environments. These volatile emissions have been demonstrated to show a high degree of variability in response to different environmental conditions. The phyllosphere is the entire aboveground surface of a plant, which offers a suitable habitat for the life of some microorganisms. Remarkable advances are being made in the characterization of phyllospheric microbial communities and the study of their ecological roles with the help of novel genomic techniques.